High-frequency corrosion fatigue behavior of AZ31 magnesium alloy in different environments. (July 2014) - He, XL; Wei, YH; Hou, LF; Yan, ZF; Guo, CL
The high-frequency corrosion fatigue behavior of extruded AZ31 magnesium alloy was investigated in different environments: air, gear oil and 3.5% NaCl solution. Compared with that in air, the corrosion fatigue limits were degraded by approximately 3.52% and 58.91%, respectively, and the corrosion fatigue lives were shortened by about 13.43% and 89.36%, respectively. In the same environment, the high-frequency fatigue limits are all higher than those tested at low frequency. The specimen geometrical shape plays a certain factor on stage characteristics of S–N curves. Compared with that of arc transition specimens, the stress sensitivity of line transition specimens is only reflected in a relatively high cycle fatigue life region. Different environments influence the corrosion failure kinetics processes (the crack initiation mechanism), but do not change the fatigue fracture mechanism of the alloy, and the higher loading frequency only accelerate the crack nucleation processes.